Development of a pulse solenoid of magnetic field amplitude up to 0.5 T and a pulse sinusoidal current generator for its power supply - Reshetnyak, N.G.; Romasko, V.P.; Chertishev, I.A. (Вопросы атомной науки и техники, 2020)
The magnetic system of the installation to control the transverse dimensions of an electron beam formed by a magnetron gun with a secondary emission cathode was updated. An additional solenoid with pulsed power supply located in a vacuum chamber at a distance of 0.05…0.1 m from the gun’s edge will be used in experiments. The solenoid design was selected and calculated. Possibility of a magnetic field generation of amplitude of up to 0.5 T at amplitude of the pulse current of ~ 1.5 kA, was demonstrated. The field has a uniform area at the level of ± 5% over the length of ~ 0.2 m.